Effect of Echinacea purpurea on Control of Leishmania major Induced Cutaneous Leishmaniasis in Mice - MS Sadati; B Sarkari; Q Asgari; S Hatami; E Tavakl (Armaghane Danesh Bimonthly Journal, 2011)
Introduction & Objective: Leishmaniasis is a disease caused by intracellular protozoa parasites of the genus Leishmania and is endemic in some areas of Iran. Echinacea purpurea is a native plant from North America which is one of the most important medical herbs known with immuno-stimulant properties. This study was performed to determine the effect of alcoholic extract of Echinacea purpurea on prophylaxis and treatment of Leishmania cutaneous lesions.